Analysis of the geographic pattern of the police reports for domestic violence in Girona (Spain) - Laura Serra; Laura Vall-llosera; Diego Varga; Carme Saurina; Marc Saez; Gemma Renart (BMC, 2022)
Abstract Background There are many studies that address the issue of gender-based violence, but few analyse the police-reported cases. It is as important to analyse the temporal and geographic distribution of these incidents as it is the sociodemographic profile of the accuser. To this effect, the present study aims to analyse the sociodemographic profile of the victims of the particular case of domestic violence that report the incident to the police and to evaluate the spatial-temporal distribution of these reports. Methods Using the data from a database containing the police-reported incidents of domestic violence in Girona in the period 2012-2018, the risk of a police-reported incident was estimated by adjusting the two-part Hurdle model. Results The risk of reporting incidents of domestic violence to the police is higher in the less deprived areas of the city, and the spatial distribution of these police reports corroborate this finding. Nevertheless, those areas with the greatest socio-economic deprivation were also the ones where there were less police reports filed. Also the prediction of less police reports in the census tract with the highest percentage of the population with an insufficient educational level coincides with the largest number of police reports made by women with a medium and university level education (56.1%) compared with 9.5% of police reports made by women with insufficient schooling. Conclusions These results can be useful for social protection services to design policies specifically aimed at women residing in those areas with the highest risk. Moreover, the use of spatial statistical techniques together with geographic information systems tools is a good strategy to analyse domestic violence and other types of offences because they not only allow to graphically identify the spatial distribution, but it is also a good tool to identify problems related to this type of offence.